Microstructure and ablation mechanism of C/C-ZrC-SiC composites in a plasma flame. Issue 14 (1st October 2017) - Wang, Shaolei; Li, Hong; Ren, Musu; Zuo, Yazhuo; Yang, Min; Zhang, Jiabao; Sun, Jingliang
Abstract: Ablation behavior of C/C-ZrC-SiC composites was investigated using a plasma flame. The composites exhibited excellent ablation performance. After ablation for 180 s, three kinds of ablation behavior appeared from the border to the center on the surface, which were closely related to the temperature and denudation force. Additionally, the ablation behavior in the cross-sectional direction of the composites was mainly controlled by the temperature. During the ablation, ZrC and SiC were oxidized into ZrO2 and SiO2, respectively, resulting in the formation of a ZrO2 -SiO2 binary eutectic system. The ablation mechanism was also discussed, which could provide strong illustration of the evolution processes of the eutectic system at different temperatures.